PENGARUH MODEL TEACHER CENTERED LEARNING TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 2 SOSOPAN KABUPATEN PADANG LAWAS - Darliana Sormin; Jumaita Nopriani Lubis; Lily Zefrina Hasibuan; Mulyadi Hermanto Nst; Mira Rahmayanti Sormin; Rahmah Yasrah Dalimunthe (Jurnal Al-Fatih, 2025)
This study aims to determine how much influence of the Teacher Centered Learning Model has on the learning outcomes of Islamic religious education at SMP Negeri 2 Sosopan, Padang Lawas Regency. This type of research is quantitative, which is a research method using standardized measurements or using a data measurement scale. The population used is all class VIII in SMP Negeri 2 Sosopan, Padang Lawas Regency. The sampling technique was Simple Random Sampling so that the sample in this study was class VIII-1 which amounted to 34 students. Data collection techniques are tests, questionnaires and documentation. The hypothesis test used is the Simple Linear Regression test. From the test results hypothesis obtained a P-Value value of 0.014 so that the regression coefficient is 0.014 ≤ 0.05. Then the Teacher Centered Learning Model affects the learning outcomes of Islamic Religious Education. Big influence of the Teacher Centered Learning Model on Learning Outcomes seen from the Determination (R Square) of 0.92 or 92% affects the learning outcomes of Islamic Religious Education. So that it can betaken conclusion that the hypothesis is accepted “The Teacher Centered Learning Model effects the Learning Outcomes of Islamic Religious Education at SMP Negeri 2 Sosopan, Padang Lawas Regency.”